Globalization and Medical Tourism: The North American Experience; Comment on "Patient Mobility in the Global Marketplace: A Multidisciplinary Perspective" - Arturo Vargas Bustamante (Kerman University of Medical Sciences, 2014)
Neil Lunt and Russel Mannion provide an overview of the current state of the medical tourism literature and propose areas for future research in health policy and management. The authors also identify the main unanswered questions in this field ranging from the real size of the medical tourism market to the particular health profiles of transnational patients. In addition, they highlight unexplored areas of research from health economics, ethics, policy and management perspectives. To this very insightful editorial I would add the international trade perspective. While globalization has permeated labor and capital, services such as healthcare are still highly regulated by governments, constrained to regional or national borders and protected by organized interests. Heterogeneity of healthcare regulations and lack of cross-country reciprocity agreements act as barriers to the development of more widespread and dynamic medical tourism markets. To picture these barriers to transnational health services I use evidence from North America, identifying different "pull and push factors" for medical tourist in this region, discussing how economic integration and healthcare reform might shift the incentives to utilize healthcare abroad.